2020
DOI: 10.1016/j.enconman.2020.113161
|View full text |Cite
|
Sign up to set email alerts
|

A rule-based energy management scheme for long-term optimal capacity planning of grid-independent microgrid optimized by multi-objective grasshopper optimization algorithm

Abstract: Highlights A nature-inspired driven approach is proposed to optimally design off-grid microgrid. Development of a rule-based energy management scheme based on queuing theory. The optimization problem minimizes energy cost and maximizes system reliability. The proposed grasshopper optimization algorithm is compared with PSO and CSA. The performance of the microgrid has been analysed against future uncertainties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…The system was composed of PV panels, battery systems, an electric vehicle (EV), and a relay board, which allowed or rejected the power fluxes according to certain rules aimed at minimizing the energy consumption from the public grid. Another similar work can be found in [73], in which an REMS with a nature-inspired grasshopper optimization algorithm (GOA) was presented. This optimization method was aimed at minimizing the cost of energy (COE) and the probability of the deficiency of energy supply.…”
Section: Ems Based On Metaheuristic Methodsmentioning
confidence: 99%
“…The system was composed of PV panels, battery systems, an electric vehicle (EV), and a relay board, which allowed or rejected the power fluxes according to certain rules aimed at minimizing the energy consumption from the public grid. Another similar work can be found in [73], in which an REMS with a nature-inspired grasshopper optimization algorithm (GOA) was presented. This optimization method was aimed at minimizing the cost of energy (COE) and the probability of the deficiency of energy supply.…”
Section: Ems Based On Metaheuristic Methodsmentioning
confidence: 99%
“…The scope of this work is oriented towards tertiary control. Various research works dedicated to tertiary control are reported in [7,18,19].…”
Section: The Hes Architecture and Modeling In Stateflowmentioning
confidence: 99%
“…The component G i from the centered equation can be computed as; Gi=geg, where g is the acceleration constant of gravity and eg is a unit vector, directing towards the center of the earth. Figure 17 depicts the strength of social force by varying the values of intensity of attraction and the attractive length scale 94 …”
Section: Meta‐heuristic Optimization Algorithmsmentioning
confidence: 99%